Anti-Suicidal Efficacy of Repetitive Transcranial Magnetic Stimulation in Depressive Patients: A Retrospective Analysis of a Large Sample - Abdelnaim, Mohamed A.; Langguth, Berthold; Deppe, Markus; Mohonko, Alexey; Kreuzer, Peter M.; Poeppl, Timm B.; Hebel, Tobias; Schecklmann, Martin (Frontiers in Psychiatry, 2020)
Background: Suicide is a major public health problem. About 90% of suicide victims have one or more major psychiatric disorder, with a reported 20-fold increased risk for suicide in patients with affective disorders in comparison with healthy subjects. Repetitive transcranial magnetic stimulation (rTMS) has been established as an effective alternative or adjunctive treatment option for patients with depressive disorders, but little is known about its effects on suicide risk. Objective: For the assessment of the effectiveness of rTMS on suicidal ideation and behaviors, we performed a retrospective analysis of a large sample of patients with depressive disorders, who were treated with rTMS. Methods: We analyzed the records of 711 TMS in- and out-patients with depressive affective disorders in a tertiary referral hospital between 2002 and 2017. Out of these patients we were able to collect Hamilton depression rating scale (HAMD) data of 332 patients (180 females,152 males; age range 20 to 79 years; mean age 47.3±12.3) for which we analysed the change of suicidal ideation by using item 3 (suicidality) of HAMD. Results: Out of all 711 patients treated with rTMS for their depression, one patient (0.1%) committed suicide during the TMS treatment. In the statistical analysis of the subsample with 332 patients there was an overall amelioration of depressive symptoms accompanied by a significant decrease in the suicidality item with a medium effect size. Decrease in suicidality was not inferior to changes in other items as indicated by effect sizes. 47.0% of patients showed an amelioration in suicidality, 41.3% of patients did not show a change in their suicidality’s scores and 11.7% of patients showed an increase in suicidality’s scores from baseline to final rating. Correlation of item 3 (suicidality) and item 7 (drive) demonstrated a significant positive association, revealing improved drive with a parallel decreased suicidality. Conclusion: Based on the proposed data, there is no evidence that rTMS increases the risk for suicide during the course of the treatment. Conversely, rTMS tends to reduce suicidal ideation. Our findings call for further rTMS controlled studies using large sample sizes and specific suicidality assessment measures to obtain more conclusive results.